Efficiency of AUY922 in mice with adult T-cell leukemia/lymphoma - ISHIKAWA, CHIE (Oncol Lett, 2016)
Adult T-cell leukemia/lymphoma (ATLL) is an aggressive malignancy caused by human T-cell leukemia virus type 1 (HTLV-1). ATLL is associated with poor prognosis mainly due to resistance to chemotherapy, which highlights the requirement for alternative therapies. The chaperone heat shock protein (HSP) 90 assist proteins involved in the onset and progression of ATLL. In the present study, the efficacy of a second generation HSP90 inhibitor termed AUY922 was investigated in ATLL. In vitro, AUY922 induced marked inhibition of cell viability in the HTLV-1-infected T-cell lines HUT-102 and MT-4. In immunodeficient mice bearing HUT-102 xenotransplants, AUY922 markedly retarded tumor growth, compared with the control group. Apoptosis was evident in hematoxylin and eosin stained- and terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick end labeling-labeled tissue sections from AUY922-treated mice. In addition, AUY922 significantly reduced the serum levels of the surrogate tumor markers soluble interleukin-2 receptor and soluble cluster of differentiation 30. Overall, the present results demonstrate that AUY922 has potent anti-ATLL activity, thus providing a rationale for continuing the clinical development of HSP90 inhibitors in clinical trials for the treatment of patients with ATLL.